INTERNET MOBILITY, CO-PRESENCE AND PURPOSE: CONTEXTUALISING INTERNATIONALISATION IN RESEARCH CAREERS (Sociología y tecnociencia, 2013)
This paper addresses the role that co-presence plays in the process of researcher and research internationalisation. Put simply, it considers how much time researchers need to spend in particular places (outside of their own country) in order to generate optimal conditions for knowledge creation and transfer. Drawing on empirical evidence gleaned from a range of recent research projects, it suggests that the need for co-presence is highly contextualised reflecting disciplinary and field-specific considerations.On the basis of this evidence, the paper critiques the received wisdom that permeates research policy in many national contexts equating excellence with internationalisation, and internationalisation with physical (and usually long stay) mobility. In so doing, it supports a growing concern that ‘researcher mobility should never be seen as an end-point in itself’ (ESF, 2013b:3). It builds on the author’s previous work on the relationship between gender, mobility and career progression (Ackers, 2008; 2010). This work, supported by that of other authors such as Cox (2008), established the importance of a growing ‘mobility imperative’ to the career progression of women. It also highlighted the role that the progressive institutionalisation of metrics associated with internationalisation was playing in this process (Ackers and Gill, 2008).Supporting a more evidence-based and nuanced approach to internationalisation, metrics goes some way to remove unintended consequences or discriminatory outcomes (Ackers, 2008) and to encourage a more merit-based approach to researcher evaluation.